2013
DOI: 10.1186/1746-6148-9-89
|View full text |Cite
|
Sign up to set email alerts
|

Purification of pregnancy-associated glycoproteins from late-pregnancy Bubalus bubalis placentas and development of a radioimmunoassay for pregnancy diagnosis in water buffalo females

Abstract: BackgroundPregnancy-associated glycoproteins (PAGs) were first described as placental antigens present in the blood serum of the mother soon after implantation. Here, we describe the purification of several pregnancy-associated glycoproteins from water buffalo placenta (wbPAGs). A specific radioimmunoassay (RIA) was developed for early pregnancy diagnosis in buffalo species.ResultsAmino-terminal microsequencing of immunoreactive placental proteins allowed the identification of eleven wbPAGs sequences [Swiss-Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…This is a similar trend to that described by Gajewski et al [46] for Berrichon ewes, by Ledezma-Torres et al [14] for various sheep breeds and by Ranilla et al [11,24] for Churra sheep, yet this trend was not observed for Merinos ewes whose PAG levels initially increased and then dropped to baseline concentrations around mid-pregnancy. Patterns of plasma ovine PAG concentrations differed from those reported for bovine [30], goats [47,48] and buffalo [20,49]. These differences could be explained by the ability of the antisera to distinguish between various epitopes [20].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This is a similar trend to that described by Gajewski et al [46] for Berrichon ewes, by Ledezma-Torres et al [14] for various sheep breeds and by Ranilla et al [11,24] for Churra sheep, yet this trend was not observed for Merinos ewes whose PAG levels initially increased and then dropped to baseline concentrations around mid-pregnancy. Patterns of plasma ovine PAG concentrations differed from those reported for bovine [30], goats [47,48] and buffalo [20,49]. These differences could be explained by the ability of the antisera to distinguish between various epitopes [20].…”
Section: Discussionmentioning
confidence: 71%
“…These molecules are present in maternal plasma of sheep in concentrations detectable with RIA methods as early as 18-20 days after conception, [3,[11][12][13][14][15][16] and by the enzyme immune assay (EIA) method [17][18][19], as well as in other species of ruminants [1,[20][21][22]. Throughout pregnancy, PAG concentrations in these species differ according to the breed, fetal number, sex and birth weight [3,[23][24][25][26][27][28][29], as in other ruminants [30].…”
Section: Introductionmentioning
confidence: 99%
“…Using various chromatographic procedures, some members of the PAG family have been isolated from the cotyledons of several species of the order Cetardiodactyla (Beriot, Tchimbou, Barbato, Beckers, & Sousa, 2014;Brandt, Parks, Killian, Ealy, & Green, 2007;El Amiri et al, 2004;Garbayo et al, 1998;Green et al, 2000;Majewska, Panasiewicz, Majewski, & Szafranska, 2006;Sousa et al, 2003;Szafranska et. al., 1995;Xie et al, 1997;Zoli et al, 1991) including water buffalo (wbPAG; Barbato, Melo de Sousa, Barile, Canali, & Beckers, 2013;Barbato et al, 2008).…”
mentioning
confidence: 99%
“…Our research group (Barbato et al, 2016(Barbato et al, , 2013 reported using antisera raised against buffalo PAG molecules, purified from buffalo placenta, to develop a specific RIA system (RIA-860) for pregnancy diagnosis in buffalo. Using this system, the plasma PAG profiles of water buffalo during pregnancy and postpartum periods have been recently described (Barbato et al, 2017).…”
mentioning
confidence: 99%
“…Transrectal ultrasonography (Aloka -SSD500 scanner equipped with 7.5 MHz linear-array transducer) confirmed pregnancy status and embryo viability (heartbeat visualization) on 28 d, 40 d and 56 d. All ultrasound scans were performed by the same operator. PAG RIA plasma concentrations were determined in duplicate, as previously described by Barbato et al (2013). The specific antibody was an anti buffalo PAG73kDa serum (AS#860) raised in rabbit.…”
Section: Pregnancy Diagnosismentioning
confidence: 99%